1991
DOI: 10.1071/ea9910001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of conception rate in extensive beef herds in north-western Australia. 1. Seasonal mating and improved management

Abstract: Statistical models for conception rate were developed using data collected at a mid dry season (August-September) muster from a controlled-mated and supplemented herd of 900 Brahman cross cows at Mt Bundey from 1980-84. Average conception rates were 74% for maidens, 25% for first-lactation cows, 51 % for 4-10-year-old lactating cows, 54% for >10-year-old lactating cows and 96% for non-lactating cows. Although year effects dominated, they were partially explained by severity of the dry season and were consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, Morley et al (1976), from an analysis of results for groups of mature Angus cows grazing at different stocking rates, found an increase in the probability of pregnancy with mean weight at joining that amounted to 0.14 per unit of CS. Responses to CS are even more marked in extensive beef herds in north-western Australia (O'Rourke et al 1991). Graham and Clarke (1984) showed that CS is a good indicator of fat depth on live cattle, and therefore a useful aid in sales-by-description of animals for slaughter.…”
Section: Relationships Between Cs and Productionmentioning
confidence: 99%
“…However, Morley et al (1976), from an analysis of results for groups of mature Angus cows grazing at different stocking rates, found an increase in the probability of pregnancy with mean weight at joining that amounted to 0.14 per unit of CS. Responses to CS are even more marked in extensive beef herds in north-western Australia (O'Rourke et al 1991). Graham and Clarke (1984) showed that CS is a good indicator of fat depth on live cattle, and therefore a useful aid in sales-by-description of animals for slaughter.…”
Section: Relationships Between Cs and Productionmentioning
confidence: 99%
“…Osoro and Wright (1992) and De Rouen et al (1994), concluded that BCS at calving significantly affected postpartum reproductive performance in cows. O'Rourke et al (1991) reported that cows with BCS of ≥8 had a conception rate 33% higher than those with score ≤5 (scale 3-9). Buffaloes in poor BCS had inactive ovaries and long postpartum anoestrus periods (Jainudeen and Wahab, 1987).…”
Section: Body Condition Scorementioning
confidence: 99%